2006
DOI: 10.1128/jvi.80.7.3189-3204.2006
|View full text |Cite
|
Sign up to set email alerts
|

Acetylated Tat Regulates Human Immunodeficiency Virus Type 1 Splicing through Its Interaction with the Splicing Regulator p32

Abstract: The human immunodeficiency virus type 1 (HIV-1) potent transactivator Tat protein mediates pleiotropic effects on various cell functions. Posttranslational modification of Tat affects its activity during viral transcription. Tat binds to TAR and subsequently becomes acetylated on lysine residues by histone acetyltransferases. Novel protein-protein interaction domains on acetylated Tat are then established, which are necessary for both sustained transcriptional activation of the HIV-1 promoter and viral transcr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
92
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 87 publications
(93 citation statements)
references
References 103 publications
1
92
0
Order By: Relevance
“…In addition, P32 plays a role in the regulation of the life cycle of several viruses such as HIV or cytomegalovirus (22,23). Consistent with the large diversity of its functions, P32 is localized to different subcellular compartments, such as mitochondria, to the outer cell membrane, or to the nucleus (24).…”
mentioning
confidence: 84%
“…In addition, P32 plays a role in the regulation of the life cycle of several viruses such as HIV or cytomegalovirus (22,23). Consistent with the large diversity of its functions, P32 is localized to different subcellular compartments, such as mitochondria, to the outer cell membrane, or to the nucleus (24).…”
mentioning
confidence: 84%
“…It seems unlikely that this second Tat function involves binding to TAR RNA, since the Tat-TAR binding study demonstrated that the mutations in the SIV-rtTA TAR element prevent Tat binding. Multiple additional roles for Tat have been suggested in HIV-1 biology; for example, Tat has been reported to affect mRNA capping, splicing, and translation (14,18,20,21,23,67,69,78), to stimulate reverse transcription (1,36,37,42,43,71), and to suppress RNA interference (7,35). Moreover, Huang et al demonstrated that HIV-1 variants regulated by the Gal4-VP16 transactivator protein require Tat for infectivity (38), and we recently observed that the introduction of a frameshift mutation in the HIV-1 Tat gene, which prevents Tat production, abolished HIV-rtTA replication.…”
Section: Discussionmentioning
confidence: 99%
“…HLM-1 cells are HeLa-T4 ϩ cells containing one integrated copy of the HIV-1 genome with a Tat-defective mutation at the first AUG of the Tat gene. In the absence of stimulation, HLM-1 is completely negative for virus particle production, and viral transcripts are completely absent (83). Suspensions of J1.1 and ACH2 cells and their uninfected counterparts, Jurkat and CEM cells, as well as the promonocytic U1 cell line and the corresponding uninfected U937 cell line, were cultured in RPMI 1640 medium supplemented with 10% heat-inactivated FBS, 1% L-glutamine, and 1% streptomycin/penicillin.…”
Section: Methodsmentioning
confidence: 99%